2015
DOI: 10.1371/journal.pone.0126553
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patient Empowerment - A Systematic Review of Measures

Abstract: BackgroundPatient empowerment has gained considerable importance but uncertainty remains about the best way to define and measure it. The validity of empirical findings depends on the quality of measures used. This systematic review aims to provide an overview of studies assessing psychometric properties of questionnaires purporting to capture patient empowerment, evaluate the methodological quality of these studies and assess the psychometric properties of measures identified.MethodsElectronic searches in fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
200
1
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(223 citation statements)
references
References 67 publications
2
200
1
20
Order By: Relevance
“…The active participation of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Finally, from an organizational perspective, although there is no universally agreed measure of SDM, there are some proposed solutions at different levels (micro, meso or macro level) to overcome key challenges to measure SDM (Barr, Scholl, et al 2016). In particular, it would be useful for organizations: to involve patients and healthcare professionals in designing, developing and testing measures; to build strategies to include patient-reported outcomes in organizational registries (e.g., electronic medical records); to set up automated analysis methods to provide rapid feedback and methods of monitoring SDM in clinical encounters (to service users, mental health professionals, multidisciplinary teams care, organizations and health care systems); to set aside staff time to measure and monitor key outcomes; and finally, to promote tools as a component of a continuous monitoring set of routines, and build the tools into balanced scorecard when the value of measuring may not be recognized (Barr et al, 2015;Metz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The active participation of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Finally, from an organizational perspective, although there is no universally agreed measure of SDM, there are some proposed solutions at different levels (micro, meso or macro level) to overcome key challenges to measure SDM (Barr, Scholl, et al 2016). In particular, it would be useful for organizations: to involve patients and healthcare professionals in designing, developing and testing measures; to build strategies to include patient-reported outcomes in organizational registries (e.g., electronic medical records); to set up automated analysis methods to provide rapid feedback and methods of monitoring SDM in clinical encounters (to service users, mental health professionals, multidisciplinary teams care, organizations and health care systems); to set aside staff time to measure and monitor key outcomes; and finally, to promote tools as a component of a continuous monitoring set of routines, and build the tools into balanced scorecard when the value of measuring may not be recognized (Barr et al, 2015;Metz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it would be useful for organizations: to involve patients and healthcare professionals in designing, developing and testing measures; to build strategies to include patient-reported outcomes in organizational registries (e.g., electronic medical records); to set up automated analysis methods to provide rapid feedback and methods of monitoring SDM in clinical encounters (to service users, mental health professionals, multidisciplinary teams care, organizations and health care systems ); to set aside staff time to measure and monitor key outcomes; and finally, to promote tools as a component of a continuous monitoring set of routines, and build the tools into balanced scorecard when the value of measuring may not be recognized (Barr et al 2015;Metz et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a previous review [16] found significant methodological shortcomings in the available measures, mainly due to a lack of clarity on the PE concept. Finally, despite all these efforts to improve PE definitions and measures, the latest (Canadian) review concluded that there is still a lack of conceptual clarity in PE research [17].…”
Section: Definition Measure Terminology and Diseasementioning
confidence: 99%
“…It was also developed using a validity driven approach [12], and measures proximal outcomes related to selfmanagement behavior across 8 dimensions. The heiQ has been found to capture dimensions strongly related to empowerment [21]. A Canadian study [22] and a recent Danish review suggests that five of the eight dimensions of heiQ, including; 3.…”
Section: Introductionmentioning
confidence: 99%